Trinitas Menurut Tertullianus dalam Buku Against Praxeas - Suhassatya, Gabriel Kristiawan (Institutum Theologicum Ioannis Mariae Vianney Surabayanum, 2022)
The debate about the Triune God or the Trinity has existed since the time of the early Church Fathers until today. The notion of a three-person God raises many questions and debates. The debate about the Trinity has emerged in the practice of the Christian faith since the time of the Church Fathers. Inevitably this prompted the Church Fathers to formulate and always defend their faith in the Triune God, namely by believing and learning so that it can be explained to everyone. Efforts to formulate and explain the understanding of the Triune God or the Trinity was also carried out by Tertullianus. Tertullian was an early Church Father from Africa who gave many defenses and resistances against heretical teachings that contradicted Christian teachings. In addition to defending the faith, it was Tertullian who gave the name Trinity for the Triune God, namely One God with Three Persons. In this paper, the author describes the life story of Tertullianus, the theological problems that arose during Tertullian's time, and the origin of Tertullian's thoughts on the concept of the Trinity.